A high-strength, high-toughness and high-hardness polyolefin and its application
By adjusting the molar ratio and molecular structure of α-olefins through copolymers of ethylene or propylene and a variety of mixed α-olefins, the problem of difficulty in achieving high strength, high toughness and high hardness at the same time is solved, and the synchronous improvement of the strength, toughness and hardness of polyolefin materials is achieved.
Patent Information
- Application Number
- CN202310783538.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-06-29
AI Technical Summary
It is difficult for existing polyolefin elastomer materials to achieve high strength, high toughness and high hardness at the same time.
A copolymer of ethylene or propylene and a variety of mixed α-olefins is used to form a high-strength, high-strength, high-hardness, and high-hardness polyolefin copolymer by adjusting the molar ratio and molecular structure of the α-olefins.
It has achieved synchronous improvement of strength, toughness and hardness of polyolefin materials, and has the advantages of easy processing, outstanding toughening effect, high cross-linking efficiency, good processing temperature and compatibility matching.
Smart Images

Figure BDA0004311508950000061 
Figure BDA0004311508950000062 
Figure BDA0004311508950000071
Abstract
Description
Technical Field
[0001] The invention relates to a polyolefin product, in particular to a high-strength, high-toughness and high-hardness polyolefin copolymer and application thereof. Background Art
[0002] Polyolefin elastomer (POE) is a copolymer of ethylene or propylene and α-olefin, and the α-olefin content is often higher than 6 mol% or 20wt%. The higher the α-olefin content, the lower the density of the POE product, the lower the crystalline content, the smaller the lamella size, the smaller the tensile strength, the higher the elongation at break, and the lower the hardness. Therefore, it is difficult for ordinary polyolefin elastomers to achieve high strength, high toughness and high hardness at the same time.
[0003] In order to achieve simultaneous enhancement of strength, toughness and hardness, Dow used chain shuttling technology, tridentate pyridine amino hafnium and phenoxy cycloalkyl imine FI-Zr as catalysts, diethyl zinc or dialkyl magnesium as chain shuttling agents, and developed an ethylene / 1-octene multi-block copolymer OBC. The ethylene homopolymer segment with extremely low α-olefin content has the characteristics of high melting point, high strength and high hardness, and the ethylene / octene copolymer segment with high α-olefin content has good toughness. However, the chain shuttling technology used by Dow has extremely high technical barriers, and it is difficult to prepare polyolefin materials with high strength, high toughness and high hardness with a single catalyst. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a polyolefin copolymer with high strength, high toughness and high hardness, which is a copolymer of ethylene or propylene and a variety of mixed α-olefins, which can solve the problem in the prior art that the strength, toughness and hardness of polyolefin elastomer materials are difficult to enhance simultaneously.
[0005] According to one object of the present invention, the present invention provides a high-strength, high-toughness and high-hardness polyolefin copolymer, which is a copolymer of ethylene or propylene and three different α-olefins, wherein the α-olefin is selected from α-olefins with more than 3 carbon atoms and less than 12 carbon atoms; the content of the ternary segment structure I composed of three consecutive α-olefin units in the polyolefin copolymer is 0.001 mol%-3 mol%; the three α-olefins are α-olefin A, α-olefin B, and α-olefin C according to the number of carbon atoms from small to large, and in the polyolefin copolymer, the molar ratio of α-olefin A, α-olefin B, and α-olefin C is (0.1-2.5):1:(0.1-4.0).
[0006] According to a preferred embodiment of the present invention, the weight average molecular weight of the polyolefin copolymer is 3-400 kg / mol, and the molecular weight distribution index is 1.1-5.0; the melting temperature of the polyolefin is 30-110°C; the tensile strength at break of the polyolefin is 1-30 MPa; the polyolefin has no fracture phenomenon in the impact test at room temperature and -20°C; the Shore A hardness of the polyolefin is 45-90. Preferably, in the polyolefin copolymer provided by the present invention, the weight average molecular weight is 30-300 kg / mol, the molecular weight distribution index is 1.3-3.5; the melting temperature of the polyolefin is 35-100°C. More preferably, in the polyolefin copolymer provided by the present invention, the tensile strength at break is 2.2-26 MPa, the glass transition temperature is -40 to -60°C, and the Shore A hardness of the polyolefin is 50-85.
[0007] In the high-strength, high-toughness and high-hardness polyolefin copolymer provided by the present invention, the α-olefin is preferably selected from two or more of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene and 1-decene. Further, the α-olefin is selected from three of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene and 1-decene, and there is at least one α-olefin with an odd number of carbon atoms. Specifically, the α-olefin is selected from three of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene, and there is at least one α-olefin with an odd number of carbon atoms, and the three α-olefins are olefin A, olefin B, and olefin C (the number of carbon atoms of A is less than the number of carbon atoms of B, and the number of carbon atoms of B is less than the number of carbon atoms of C), and the A / B / C mixed α-olefin is preferably 1-butene / 1-pentene / 1-hexene, 1-butene / 1-pentene / 1-heptene, 1-butene / 1-pentene / 1-octene, 1-butene / 1-pentene / 1-nonene, 1-butene / 1-hexene / One of 1-heptene, 1-butene / 1-hexene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-nonene, 1-pentene / 1-hexene / 1-heptene, 1-pentene / 1-hexene / 1-octene, 1-pentene / 1-hexene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-octene / 1-nonene, 1-hexene / 1-heptene / 1-octene, 1-hexene / 1-heptene / 1-nonene, 1-heptene / 1-octene / 1-nonene.
[0008] According to one aspect of the present invention, in the polyolefin copolymer, the molar ratio of α-olefin A, α-olefin B, and α-olefin C is (0.1-2.5):1:(0.3-3.0), preferably (0.5-2.5):1:(0.3-3.0), and the molar ratio of α-olefin to ethylene or propylene is (0.1-1.0):1.
[0009] According to one aspect of the present invention, the content of ternary segment structure I composed of three consecutive α-olefin units in the polyolefin copolymer (i.e., AAA+AAB+AAC+ABA+ABB+ABC+ACA+ACB+ACC+BAA+BAB+BAC+BBA+BBB+BBC+BCA+BCB+BCC+CAA+CAB+CAC+CBA+CBB+CBC+CCA+CCB+CCC fragment structure) is 0.001 mol%-3 mol%, and the content of ternary segment structure II composed of two consecutive α-olefin units and one ethylene unit (i.e., EAA+EAB+EAC+EBA+EBB+EBC+ECA+ECB+ECC+AAE+ABE+ACE+BAE+BB The content of the ternary segment structure III composed of two discontinuous α-olefin units and one ethylene unit (i.e., the AEA+AEB+AEC+BEA+BEB+BEC+CEA+CEB+CEC fragment structure) is between 0.01 mol% and 15 mol%, and the content of the ternary segment structure IV composed of three continuous ethylene units (i.e., the EEE fragment structure) is between 50 mol% and 90 mol%.
[0010] In a specific embodiment of the present invention, the polyolefin is prepared by a high-temperature solution polymerization process, the temperature of the solution polymerization process is 100-180°C, the pressure is 10-50 bar, the catalyst is selected from one or more of a metallocene catalyst, a late transition metal catalyst, a Ziegler-Natta catalyst, a non-metallocene catalyst, and a FI catalyst, and the co-catalyst is selected from one or more of methylaluminoxane MAO, modified methylaluminoxane MMAO, ethylaluminoxane EAO, butylaluminoxane BAO, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, and tri(2,4,6-trifluorophenyl)borane. In the polymerization, the polymerization monomers are ethylene and α-olefins, and the molar ratio of the added amounts of α-olefin A, α-olefin B, and α-olefin C is (0.1-2.5):1:(0.1-4.0), preferably (0.1-2.5):1:(0.3-3.0), and more preferably (0.5-2.5):1:(0.3-3.0), and the molar ratio of α-olefin to ethylene or propylene is (0.1-1.0):1.
[0011] Furthermore, the catalyst can be pre-dissolved and complexed with an appropriate amount of nucleating aid during the preparation stage, the complexation time is 1 min-2 h, the molar ratio of the catalyst to the nucleating aid is 1: (1-100), and then added to the polymerization reactor. The nucleating aid is selected from one or more of aliphatic carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates, lignin acid and its derivatives, sodium benzoate and bis (p-tert-butylbenzoic acid) carboxyl aluminum, polybutylene terephthalate, poly 3-methylbutene-1, and polyvinyl cyclosilane.
[0012] Another object of the present invention is to provide the application of the high-strength, high-toughness and high-hardness polyolefin copolymer in the fields of strengthening and toughening general polyolefin materials, photovoltaic adhesive films, seals, shoe materials, hot melt adhesives, etc. The polyolefin copolymer has the advantages of easy processing, outstanding strengthening and toughening effects, high cross-linking efficiency, and good matching of processing temperature and compatibility.
[0013] The present invention has the following outstanding benefit effects: (1) With the addition of multi- or ternary mixed α-olefins, high-carbon-number α-olefins are more inserted into the molecular chain, which is beneficial to enhancing the flexibility of the molecular chain and the high elastic properties of the polyolefin copolymer; (2) Low-carbon-number α-olefins are less inserted into the molecular chain, which is beneficial to forming longer and more EEE polyethylene chain segment structures, enhancing the size and content of the crystal region, and improving the strength and hardness of the polyolefin copolymer; (3) By adjusting the insertion ratio of high-carbon-number α-olefins and low-carbon-number α-olefins in the copolymer molecular chain, the controllable optimization of the molecular chain structure can be achieved, and then the optimization of the aggregated structure can be achieved, thereby achieving the simultaneous improvement of the strength, toughness and hardness of the polyolefin copolymer. DETAILED DESCRIPTION
[0014] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0015] The following methods were used to test the structure or properties of the polyolefins produced in the examples described:
[0016] High temperature gel permeation chromatography (GPC) is used to test the molecular weight and distribution index of polyolefins.
[0017] Differential Scanning Calorimetry (DSC) is used to measure the melting point and glass transition temperature of polyolefins.
[0018] Universal testing machine is used to test the tensile strength and elongation at break of polyolefins.
[0019] Impact testing machine is used to test the impact strength of polyolefin materials.
[0020] Durometer is used to test the hardness of polyolefin materials.
[0021] Nuclear Magnetic Resonance Spectrometer ( 13 C-NMR) is used to test the α-olefin insertion rate of polyolefin materials.
[0022] Example 1
[0023] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of metallocene catalyst and 4 mg of dibenzylidene sorbitol (DBS) were dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 130°C, and 1L of hexane, 300 mL of mixed α-olefins, including 80 mL of 1-pentene, 100 mL of 1-hexene, and 120 mL of 1-heptene were added in sequence, and then 2 mmol of co-catalyst methylaluminoxane and 2 μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 30 bar, and the polymerization was carried out for 30 minutes. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0024] Example 2
[0025] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of metallocene catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 110°C, and 1L of hexane, 450 mL of mixed α-olefins were added in sequence, including 80 mL of 1-pentene, 120 mL of 1-hexene, and 250 mL of 1-octene. Then, 1.6 mmol of co-catalyst methylaluminoxane and 2 μmol of metallocene catalyst were added in sequence. Ethylene was introduced at an ethylene pressure of 20 bar and polymerization was performed for 20 minutes. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0026] Example 3
[0027] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of metallocene catalyst and 3 mg of aromatic carboxylic acid metal compound were dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 160°C, and 1L of hexane, 600 mL of mixed α-olefins were added in sequence, including 260 mL of 1-pentene, 200 mL of 1-hexene, and 140 mL of 1-nonene. Then, 2 mmol of co-catalyst methylaluminoxane and 2 μmol of metallocene catalyst were added in sequence. Ethylene was introduced at an ethylene pressure of 40 bar and polymerization was performed for 30 minutes. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0028] Example 4
[0029] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of non-metallocene catalyst and 2 mg of polyvinyl cyclosilane were dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 180°C, and 1L of hexane, 1200 mL of mixed α-olefins were added in sequence, including 100 mL of 1-hexene, 350 mL of 1-heptene, and 750 mL of 1-octene. Then, 1.2 mmol of co-catalyst triethylaluminum and 2 μmol of non-metallocene catalyst were added in sequence. Ethylene was introduced at an ethylene pressure of 50 bar and polymerization was performed for 40 min. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0030] Example 5
[0031] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of late transition metal catalyst and 6 mg of poly-3-methylbutene-1 were dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 130°C, and 1L of hexane, 1500 mL of mixed α-olefins were added in sequence, including 500 mL of 1-pentene, 400 mL of 1-hexene, and 300 mL of 1-octene. Then, 2 mmol of triisobutylaluminum as a co-catalyst and 2 μmol of late transition metal catalyst were added in sequence. Ethylene was introduced at an ethylene pressure of 30 bar and polymerization was performed for 20 minutes. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0032] Example 6
[0033] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of non-metallocene catalyst and 3 mg of sorbitol benzyl derivative were dissolved in 1 ml of hexane for standby use. The temperature of the polymerization reactor was adjusted to 120°C, and 1L of hexane, 400 mL of mixed α-olefins were added in sequence, including 80 mL of 1-hexene, 150 mL of 1-heptene, and 170 mL of 1-nonene. Then, 2 mmol of co-catalyst modified methylaluminoxane and 2 μmol of non-metallocene catalyst were added in sequence. Ethylene was introduced at an ethylene pressure of 15 bar and polymerization was performed for 30 min. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0034] Comparative Example 1
[0035] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of metallocene catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 130°C, 1L of hexane, 300 mL of 1-hexene, 2 mmol of co-catalyst methylaluminoxane, 2 μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 30 bar, and the polymerization was carried out for 30 min. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0036] Comparative Example 2
[0037] The commercially available polyolefin elastomer Engage 8150 from Dow was tested according to the above characterization method. The relevant characterization and performance test results of the obtained product are shown in Tables 1 and 2.
[0038] The relevant performance test results of the polyolefin products finally obtained in Examples 1-6 and Comparative Examples 1-2 are shown in Tables 1 and 2 below:
[0039] Table 1
[0040]
[0041] Note: NB means the impact test specimen is not broken, B means the impact test specimen is broken
[0042] Table 2
[0043]
[0044]
[0045] As shown in the table above, the polyolefin blends prepared in Example 1 and Comparative Example 1 have similar molecular weights and distributions. However, Example 1 is made by copolymerizing mixed α-olefins (1-pentene / 1-hexene / 1-heptene) with ethylene, and its tensile strength at break, impact properties, melting point, hardness and other properties are significantly better than those of the sample in Comparative Example 1. This is mainly because the molecular chain of the polyolefin sample of Example 1 contains more ternary segment structure IV (i.e., EEE fragment structure) and more ternary segment structures I, II and III. More ternary segment structure IV gives the material higher strength and hardness, and more ternary segment structures I, II and III give the material better toughness, that is, the microphase separation behavior of the molecular chain is further enhanced. Example 3 and Comparative Example 2 have similar molecular weights and distributions and comonomer alpha olefin insertion rates. However, Example 3 is made by copolymerizing mixed alpha olefins (1-pentene / 1-hexene / 1-nonene) with ethylene, and its tensile strength at break, impact performance, melting point and hardness are significantly better than those of the sample in Comparative Example 1, which is also due to the fact that the polyolefin sample of Example 3 has more ternary segment structures I, II, III and IV on the molecular chain. It can be seen that the polyolefin copolymer disclosed in the present invention has the characteristics of high strength, high toughness and high hardness, which is significantly better than commercial polyethylene elastomer materials on the market, and can be widely used in the fields of strengthening and toughening general polyolefin materials, photovoltaic adhesive films, seals, shoe materials, hot melt adhesives, etc.
[0046] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high-strength, high-toughness and high-hardness polyolefin, characterized in that: It is a copolymer of ethylene or propylene and three different α-olefins, wherein the α-olefin is selected from α-olefins with more than 3 carbon atoms and less than 12 carbon atoms; the content of the ternary segment structure I composed of three consecutive α-olefin units in the polyolefin copolymer is 0.001 mol%-3 mol%; the three α-olefins are α-olefin A, α-olefin B, and α-olefin C in order of carbon atom number from small to large, and in the polyolefin copolymer, the molar ratio of α-olefin A, α-olefin B, and α-olefin C is (0.1-2.5):1:(0.1-4.0).
2. The high-strength, high-toughness and high-hardness polyolefin according to claim 1, characterized in that: The α-olefin is selected from 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene or 1-decene, and the α-olefin having an odd number of carbon atoms is not less than one.
3. The high-strength, high-toughness and high-hardness polyolefin according to claim 2, characterized in that: The combination of three different α-olefins is 1-butene / 1-pentene / 1-hexene, 1-butene / 1-pentene / 1-heptene, 1-butene / 1-pentene / 1-octene, 1-butene / 1-pentene / 1-nonene, 1-butene / 1-hexene / 1-heptene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-nonene, 1-butene / 1-heptene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-nonene, 1-butene / 1-heptene / 1-nonene, 1-butene / 1-heptene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-nonene, 1-butene / 1-hept ...heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene / 1-heptene One of pentene / 1-hexene / 1-heptene, 1-pentene / 1-hexene / 1-octene, 1-pentene / 1-hexene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-octene / 1-nonene, 1-hexene / 1-heptene / 1-octene, 1-hexene / 1-heptene / 1-nonene, 1-heptene / 1-octene / 1-nonene.
4. The high-strength, high-toughness and high-hardness polyolefin according to claim 3, characterized in that: In the polyolefin copolymer, the molar ratio of α-olefin A, α-olefin B and α-olefin C is (0.1-2.5):1:(0.3-3.0), and the molar ratio of α-olefin to ethylene or propylene is (0.1-1.0):
1.
5. The high-strength, high-toughness and high-hardness polyolefin according to claim 3, characterized in that: In the polyolefin copolymer, the molar ratio of α-olefin A, α-olefin B and α-olefin C is (0.5-2.5):1:(0.3-3.0).
6. The high-strength, high-toughness and high-hardness polyolefin according to claim 1, characterized in that: The polyolefin is a copolymer of ethylene and three different α-olefins. In the polyolefin copolymer, the content of the ternary segment structure II composed of two continuous α-olefin units and one ethylene unit is 0.01 mol%-15 mol%, the content of the ternary segment structure III composed of two discontinuous α-olefin units and one ethylene unit is 0.01 mol%-15 mol%, and the content of the ternary segment structure IV composed of three continuous ethylene units is 50 mol%-90 mol%.
7. The high-strength, high-toughness and high-hardness polyolefin according to claim 1, characterized in that: The weight average molecular weight of the polyolefin is 3-400 kg / mol, and the molecular weight distribution index is 1.1-5.0; the melting temperature of the polyolefin is 30-110° C.; the tensile strength at break of the polyolefin is 1-30 MPa; the polyolefin has no fracture phenomenon in the impact test at room temperature and -20° C.; and the Shore A hardness of the polyolefin is 45-90.
8. The high-strength, high-toughness and high-hardness polyolefin according to claim 7, characterized in that: The weight average molecular weight of the polyolefin is 30-300 kg / mol, and the molecular weight distribution index is 1.3-3.5; the melting temperature of the polyolefin is 35-100° C., the tensile strength at break of the polyolefin is 2.2-26 MPa, the glass transition temperature is -40 to -60° C., and the Shore A hardness of the polyolefin is 50-85.
9. The high-strength, high-toughness and high-hardness polyolefin according to any one of claims 1 to 8, characterized in that: The polyolefin is prepared by a high-temperature solution polymerization process, wherein the temperature of the solution polymerization process is 100-180° C., the pressure is 10-50 bar, the catalyst is selected from one or more of a metallocene catalyst, a late transition metal catalyst, a Ziegler-Natta catalyst, a non-metallocene catalyst, and a FI catalyst, and the co-catalyst is selected from one or more of methylaluminoxane MAO, modified methylaluminoxane MMAO, ethylaluminoxane EAO, butylaluminoxane BAO, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, and tri(2,4,6-trifluorophenyl)borane.
10. The high-strength, high-toughness and high-hardness polyolefin according to claim 9, characterized in that: In the polymerization, the polymerization monomers are ethylene and α-olefins, and among the α-olefins, the molar ratio of the added amounts of α-olefin A, α-olefin B and α-olefin C is (0.1-2.5):1:(0.1-4.0).
11. The high-strength, high-toughness and high-hardness polyolefin according to claim 9, characterized in that: In the polymerization, the polymerization monomers are ethylene and α-olefins, and among the α-olefins, the molar ratio of the added amounts of α-olefin A, α-olefin B and α-olefin C is (0.1-2.5):1:(0.3-3.0).
12. The high-strength, high-toughness and high-hardness polyolefin according to claim 9, characterized in that: In the polymerization, the polymerization monomers are ethylene and α-olefins, and among the α-olefins, the molar ratio of the added amounts of α-olefin A, α-olefin B and α-olefin C is (0.5-2.5):1:(0.3-3.0).
13. The high-strength, high-toughness and high-hardness polyolefin according to claim 9, characterized in that: The catalyst is pre-dissolved and complexed with an appropriate amount of nucleating aid in the preparation stage, the molar ratio of the catalyst to the nucleating aid is 1: (1-100), and then added into a polymerization reactor; the nucleating aid is selected from one or more of aliphatic carboxylic acid metal compounds, sorbitol benzyl derivatives, aromatic carboxylic acid metal compounds, organic phosphates, lignin acid and its derivatives, sodium benzoate and bis (p-tert-butylbenzoic acid) carboxyl aluminum, polybutylene terephthalate, poly 3-methylbutene-1, and polyvinyl cyclosilane.
14. The high-strength, high-toughness and high-hardness polyolefin according to any one of claims 1 to 8 is used for strengthening and toughening general polyolefin materials, photovoltaic adhesive films, sealants, shoe materials, and hot melt adhesives.
Citation Information
Patent Citations
Preparation method of polyethylene composition, produced by gas phase fluidized bed process, for automobile fuel tanks
CN107286281A
1-butene / ethylene / advanced alpha-olefin terpolymer as well as preparation method and application thereof
CN111087511A